Characteristics and risk factors of pharmacist misconduct in New Zealand: a retrospective nationwide analysis - Yufeng Wang; Sanyogita (Sanya); Shane Scahill (BMC, 2024)
Abstract Background Professional misconduct has evolved into a worldwide concern, involving various forms and types of behaviours that contribute to unsafe practices. This study aimed to provide insights into the patterns characterising pharmacist misconduct and uncover underlying factors contributing to such instances in New Zealand. Methods This research examined all cases of pharmacist misconduct sourced from the Health Practitioners Disciplinary Tribunal (HPDT) database in New Zealand since 2004. Characteristics of the sampled pharmacists and cases were extracted, followed by a systematic coding of the observed misconduct issues. Identification of risk factors was accomplished through content analysis techniques, enabling an assessment of their prevalence across various forms of misconduct. Results The dataset of pharmacist misconduct cases comprised 58 disciplinary records involving 55 pharmacists. Seven types of misconduct were identified, with the most commonly observed being quality and safety issues related to drug, medication and care, as well as criminal conviction. A total of 13 risk factors were identified and systematically classified into three categories: (1) social, regulatory, and external environmental factors, (2) systematic, organisational, and practical considerations in the pharmacy, and (3) pharmacist individual factors. The most frequently mentioned and far-reaching factors include busyness, heavy workload or distraction; health impairment issues; and life stress or challenges. Conclusions The patterns of pharmacist misconduct are complicated, multifaceted, and involve complex interactions among risk factors. Collaborative efforts involving individual pharmacists, professional bodies, responsible authorities, policy-makers, health funders and planners in key areas such as pharmacist workload and well-being are expected to mitigate the occurrence of misconduct. Future research should seek to uncover the origins, manifestations, and underlying relationships of various contributing factors through empirical research with appropriate individuals.